2011
DOI: 10.1016/j.tsf.2011.01.289
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decomposition of NH3 on heated Ru and W surfaces

Abstract: The catalytic decomposition processes of NH 3 on heated W and Ru-coated W wires were examined by employing laser spectroscopic and mass spectrometric techniques.Laser spectroscopic measurements show that more H atoms are produced on uncoated W wires, while the NH-radical densities are higher for Ru-coated wires, at the same wire temperatures. Mass spectrometric measurements show that the decomposition efficiencies are nearly the same in both systems. The main products on heated W wires must be NH 2 and H, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…This nonlinear dependence is similar to that observed in the catalytic production of NH from NH 3 30,36) and suggests the multistep production of PH. This point will be discussed in §4.1.…”
Section: Lif Measurements Of Ph Radicalssupporting
confidence: 78%
See 1 more Smart Citation
“…This nonlinear dependence is similar to that observed in the catalytic production of NH from NH 3 30,36) and suggests the multistep production of PH. This point will be discussed in §4.1.…”
Section: Lif Measurements Of Ph Radicalssupporting
confidence: 78%
“…In the catalytic decomposition of NH 3 , we have assumed a process to produce NH from adsorbed NH 2 and H on catalyst surfaces. 36) Similar processes, such as PH 2 +H→PH+H 2 and PH+H→P+H 2 may also take place on the catalyst surfaces.…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…The absolute density was estimated by comparing the LIF intensity under saturated conditions with the intensity of Rayleigh scattering caused by Ar. This procedure was similar to those employed for the absolute density measurements of other radical species, such as Si atoms. ,,,, The differential cross section for Rayleigh scattering by Ar was calculated to be 1.31 × 10 –26 cm 2 from the wavelength, 249.8 nm, and the refractive index, 1.00031. Under saturated conditions, the population ratio of the upper 2s 2 3s 2 S 1/2 state to that of the lower 2s 2 2p 2 P 3/2 state is 1/4 when the excitation laser is linearly polarized .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…D 2 desorption was observed only from the monodeuteride species at 780 K. No PL was observed when the NCs were subjected to dissociative (thermal) adsorption of ND 3 because, as reported herein, thermal adsorption did not generate enough ND 2 and D to saturate the dangling bonds and relax the Si−Si bonds. Umemoto et al have shown that ammonia decomposition on a hot tungsten filament results in the formation of predominantly H atoms and NH 2 radicals, with NH radicals formed as a minor product . In separate experiments, a hot tungsten filament was used to predissociate ND 3 before adsorption on the NC surface .…”
mentioning
confidence: 99%
“…XPS indicates that predominantly Si-ND 2 species are adsorbed on the NC surface at these low ND 3 doses. The dissociation of NH 3 (ND 3 ) over a hot filament results in the formation of predominantly H (D) atoms and NH 2 (ND 2 ) radicals . These radicals initially passivate the dangling bonds on the NC surface at low doses, leaving the reconstructed surface dimers and steps intact.…”
mentioning
confidence: 99%